Featuring long-loop tournaments: breeding and training profiles and blood changes in criollo horses before and after exercise - Pereira, Andrielli Trentim; Pozzobon, Ricardo; dos Anjos, Bruno Leite; Kunz, Alfredo Rafael; Chaves, Leonardo Trentin; Smilgys, Erika Carla; Andrade, Bárbara da Silva; Lunkes, Vinícius Leobet; de Andrade, Cinthia Melazzo; Costa , Márcio Machado (Brazilian Journal of Veterinary Medicine, 2024)
Long-loop rodeo is a major competition for Criollo horses. We aimed to feature long-loop tournaments and to assess the profiles of competing horses. The animals (n = 49) were registered, and their body mass/scores, information about breeding, feeding, and training management, loaded weight, and tournament track (n = 11) were collected; speeds reached were estimated. Heart and respiratory rates of horses (n = 27) were collected before the tournament, on the final day of the event, and 18-24 h after the end of the tournament. Blood samples were collected from the animals at the same time. Blood count (n = 19) and biochemical profile (n = 28) were conducted based on total proteins, albumin, globulin, phosphorus, sodium, potassium, urea, creatinine, glucose, triglycerides, and cholesterol. Data were assessed using analysis of variance in association with Tukey’s test (P ≤0.05) and Spearman’s correlation (P ≤0.05). Most horses were bred in a semi-stable system, fed roughage and concentrate, and subjected to non-standardized training. The tournament comprised a high-intensity and short-duration exercise with a mean speed of 6.44 m/s, during which the horses carried 25.59% of their body weight on their backs. Clinical evaluations and hematological and biochemical assessments in this study showed physiological changes caused by exercise.